2009
DOI: 10.1021/es803143z
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Early Life Exposure to Manganese in Rural Bangladesh

Abstract: Manganese exposure and biomarker concentrations during early pregnancy and lactation were investigated in 408 women living in an area with elevated concentrations of both arsenic and manganese in drinking water derived from wells. About 40% of the water samples had manganese concentrations above the World Health Organization's guideline value and showed a strong inverse correlation with arsenic concentrations. Water manganese was found to correlate to urine concentrations, but not to blood or breast milk conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 60 publications
5
38
2
Order By: Relevance
“…1a and b). Similar behavior in tube well samples was observed with Mn, which also showed an inverse strong negative correlation with dissolved As concentrations in groundwater (Ljung et al 2009). Furthermore, a crude linear relationship was established (p<0.001) between total Cu concentrations and % solids for all swine wastewater samples (Fig.…”
Section: Resultssupporting
confidence: 72%
“…1a and b). Similar behavior in tube well samples was observed with Mn, which also showed an inverse strong negative correlation with dissolved As concentrations in groundwater (Ljung et al 2009). Furthermore, a crude linear relationship was established (p<0.001) between total Cu concentrations and % solids for all swine wastewater samples (Fig.…”
Section: Resultssupporting
confidence: 72%
“…Others have also documented high Mn exposures in this vulnerable population. A study of 408 pregnant women living in rural Bangladesh, reported that 25% were drinking water with Mn concentrations above 1000 μg/L and maternal blood Mn (erythrocyte cell portion) concentrations were higher than expected ranging from 7-53 μg/kg (32). …”
Section: Discussionmentioning
confidence: 93%
“…In order to provide manganese to the developing brain, the intestinal absorption of this element is high (Dörner et al 1989), whereas the excretion rate is low due to the incomplete development of the biliary pathway, responsible for manganese elimination (Lönnerdal 1994). However, reassuring results were found in a recent study of 408 women living in an area of Bangladesh with elevated manganese in drinking water, urine, and blood, since corresponding elevations in breast milk were not observed (Ljung et al 2009). According to the authors, elevated maternal manganese exposure does not necessarily lead to excessive exposure of breast-fed infants, stressing the importance of breast feeding in high manganese areas.…”
Section: Intravenousmentioning
confidence: 87%